2007
DOI: 10.4049/jimmunol.178.9.5839
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Stomatitis Virus Glycoprotein Displaying Retrovirus-Like Particles Induce a Type I IFN Receptor-Dependent Switch to Neutralizing IgG Antibodies

Abstract: Vesicular stomatitis virus (VSV) infection rapidly induces IFN-αβ that confers initial survival, whereas long-term protection is mediated by neutralizing IgG responses. Because coadministration of IFN-αβ can enhance Ab responses against soluble Ags, we addressed whether virus-induced IFN-αβ also had an impact on the induction of neutralizing Ab responses. To this end, we generated apathogenic retrovirus-like particles (VLP) displaying the VSV gp (VLP-VSV). Reminiscent of live VSV, VLP-VSV induced VSV-neutraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Therefore, we assayed the neutralizing capacity of the sera from latently infected mice at 4 days post VSV challenge. We observed no detectable neutralization in the IgG fraction (Fig 2A), which was consistent with previous reports (Bach et al, 2007), and likely a reflection of the time required for B-cell class-switch upon primary VSV infection. More importantly, we observed no significant difference in the neutralizing capacity of the total Ig fraction between the various groups (Fig 2B), which indicated that the difference in the neutralizing capacity of the IgG fraction at day 7 (Fig 1B) was not due to a delay in the induction of IgM responses, but rather a delayed B-cell class-switch in MCMV infected mice.…”
Section: Herpesvirus Infections Do Not Impair Initial B-cell Responsesupporting
confidence: 92%
“…Therefore, we assayed the neutralizing capacity of the sera from latently infected mice at 4 days post VSV challenge. We observed no detectable neutralization in the IgG fraction (Fig 2A), which was consistent with previous reports (Bach et al, 2007), and likely a reflection of the time required for B-cell class-switch upon primary VSV infection. More importantly, we observed no significant difference in the neutralizing capacity of the total Ig fraction between the various groups (Fig 2B), which indicated that the difference in the neutralizing capacity of the IgG fraction at day 7 (Fig 1B) was not due to a delay in the induction of IgM responses, but rather a delayed B-cell class-switch in MCMV infected mice.…”
Section: Herpesvirus Infections Do Not Impair Initial B-cell Responsesupporting
confidence: 92%
“…Of note, in this study A␤-specific Ab responses can be restimulated upon a single A␤ retroparticle boost, which suggests that retroparticle immunization may allow to considerably reduce the boost frequency to maintain sufficiently high, therapeutically effective Ab titers. In this regard, it is highly encouraging that in anti-VSV immunizations a single VSV-G retroparticle vaccination was sufficient to generate protective titers (17). However, it is also clear that in contrast to infectious diseases, anti-AD vaccination strategies will likely need to confer a certain constant minimal level of anti-A␤ Abs, as A␤ is continuously produced as a natural product of cell and brain metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that noninfectious recombinant retrovirus-like particles (retroparticles)-that do not fall under contained use regulations-can be used to display Ags at high density and that vaccination with nonreplicating retroparticles displaying either self-Ags (e.g., cellular prion protein (16)) or non-self-Ags (e.g., the glycoprotein (G) of vesicular stomatitis virus (VSV-G) (17)) induce high IgG Ab titers in the absence of adjuvant.…”
Section: A Lzheimer's Disease (Ad)mentioning
confidence: 99%
“…Activation of TLR7 and -9 by nucleic acid-containing autoimmune complexes triggers the release of IFN-a (23,24). The released amounts can reach concentrations sufficient for systemic activity and are thought to represent a perpetuating factor for autoimmunity that is continuously nourished by a positive autoamplification loop (25)(26)(27)(28): first, IFN-I-dependent gene expression primes innate immune cells for a stronger and more rapid response to exogenous and endogenous danger signals (29); second, IFN-I support a Th1 response and terminal differentiation of autoantibody-secreting B cells and class switch recombination (30)(31)(32)(33). This pluripotency of type I IFNs turns pDC into global regulators of the immune response.…”
mentioning
confidence: 99%